Mupirocin resistance patterns in staphylococcus isolates causing cutaneous and soft-tissue infections: An epidemiological study in a tertiary health-care facility, Dhule, Maharashtra, India - Karuna Ahire; Rahul Wadile; Bhanupriya Pande; Deepak Shejwal (Asian Journal of Medical Sciences, 2023)
Background: Skin and soft-tissue infections (SSI) caused by Staphylococcus aureus remain a significant concern in both community and hospital settings. Mupirocin resistance among these isolates poses challenges for infection management and control strategies. Aims and Objectives: The aim of this study was to determine the prevalence and patterns of mupirocin resistance among staphylococcus isolates responsible for cutaneous and soft-tissue infections in patients attending a tertiary health-care facility. Along with that, the study investigated into mupirocin resistance prevalence and identified risk factors. Materials and Methods: A prospective study was conducted at a medical college, including 256 non-consecutive staphylococcal isolates from SSI. Antibiotic susceptibility testing was performed using Clinical and Laboratory Standards Institute recommended methods. Mupirocin resistance was determined through disk diffusion testing using 5 μg and 200 μg Mupirocin disks for low-level and high-level resistance, respectively. Results: Among the samples, 16.4% were methicillin-resistant S. aureus (MRSA) and 9.37% were methicillin-resistant coagulase-negative staphylococci. Mupirocin high-level resistance was found in 16.6% of S. aureus isolates, and mupirocin low-level resistance in 19% of MRSA isolates. The prevalence of resistance was lower in inpatient departments compared to outpatient departments. Associations were observed between resistance and patient demographics, history of mupirocin use, surgical site infections, hospitalization history, and diabetes. Conclusion: Mupirocin resistance presents a multifaceted challenge in the context of both patient demographics and clinical settings. The prevalence of resistance was influenced by factors such as patient age, gender, and prior mupirocin usage.